Barbecue : The History of an American Institution - Moss, Robert F., 1970- (Book collections on Project MUSE., 2010)
Draws on hundreds of sources to document the evolution of barbecue from its origins among Native Americans to its present status as an icon of American culture. This is the story not just of a dish but of a social institution that helped shape the many regional cultures of the United States. The history begins with British colonists' adoption of barbecuing techniques from Native Americans in the 16th and 17th centuries, moves to barbecue's establishment as the preeminent form of public celebration in the 19th century, and is carried through to barbecue's iconic status today.